2012
DOI: 10.1007/s00228-012-1309-3
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions caused by drug–drug interactions in elderly outpatients: a prospective cohort study

Abstract: The incidence of DDI-related ADRs in elderly outpatients is high; most events presented important clinical consequences and were preventable or ameliorable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 36 publications
8
99
1
4
Order By: Relevance
“…Therefore, 15 studies with a total of 278,212 patients and 126,197 incidents of positive triggers were included in this review. 17,20,31,[33][34][35][36][37][38][39][40][41][42][43][44][45] Of the 15 included studies, 9 were conducted in the United States, 3 in Scotland, and 1 each in Brazil, France, and Australia (Table 2). Eight studies were published since 2010 and 2 were published before 2000.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, 15 studies with a total of 278,212 patients and 126,197 incidents of positive triggers were included in this review. 17,20,31,[33][34][35][36][37][38][39][40][41][42][43][44][45] Of the 15 included studies, 9 were conducted in the United States, 3 in Scotland, and 1 each in Brazil, France, and Australia (Table 2). Eight studies were published since 2010 and 2 were published before 2000.…”
Section: Resultsmentioning
confidence: 99%
“…33,36,38 -41,44 Preventable or unplanned hospital admission was the second most commonly studied type of pAE. 42,43,45 Three studies looked at any type of pAE identified in the chart. 20,31,34,35,37 The most commonly used method to identify pAEs was chart review.…”
Section: Adverse Eventsmentioning
confidence: 99%
See 3 more Smart Citations